2017
DOI: 10.14710/jkli.16.2.63-69
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Pajanan Pestisida dengan Gangguan Keseimbangan Tubuh Petani Hortikultura di Kecamatan Ngablak Kabupaten Magelang

Abstract: ABSTRAKLatar belakang, Upaya untuk meningkatkan produksi pertanian agar tanaman tidak rusak oleh hama dan penyakit petani menggunakan pestisida dengan harapan mampu meningkatkan hasil pertanian dan serta dapat membuat biaya pengelolaan pertanian menjadi lebih efisien dan ekonomis. Pestisida dapat bersifat akut, kronis maupun sistemik, yang dapat menyerang sistem syaraf ,salah satunya gangguan keseimbangan,hati atau liver,dan keseimbangan hormonal dengan cara mempengaruhi kerja enzim. Penelitian bertujuan menge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 0 publications
2
16
0
11
Order By: Relevance
“…Since the farmers did not conduct agricultural activities, especially spraying pesticides every day, work period seemed not to have a relationship to the incidence of poisoning. However, a contradictory finding was found in the study of (Samosir, K., Setiani, O., 2017) which found a relationship between work period and the incidence of pesticide poisoning.…”
Section: The Relationship Between Work Period and The Incidence Of Pementioning
confidence: 91%
See 2 more Smart Citations
“…Since the farmers did not conduct agricultural activities, especially spraying pesticides every day, work period seemed not to have a relationship to the incidence of poisoning. However, a contradictory finding was found in the study of (Samosir, K., Setiani, O., 2017) which found a relationship between work period and the incidence of pesticide poisoning.…”
Section: The Relationship Between Work Period and The Incidence Of Pementioning
confidence: 91%
“…Work period is the duration that individuals spend to work. Longer work period in farming will put farmers at more risks of contacting with pesticides (Samosir, K., Setiani, O., 2017). The exact fisher test showed that there was no meaningful relationship between work period and the incidence of pesticide poisoning.…”
Section: The Relationship Between Work Period and The Incidence Of Pementioning
confidence: 98%
See 1 more Smart Citation
“…Penelitian ini melaporkan karakteristik sampel menurut jenis kelamin yaitu jumlah sampel lakilaki lebih banyak dibandingkan perempuan yaitu 25 sampel ( (Rustia, 2010, Samosir et al, 2017.…”
Section: Karakteristik Sampelunclassified
“…Penelitian Siwiendrawati et al (2012) menunjukkan bahwa efek samping dari pestisida dapat menyebabkan wanita umur subur mengalami gangguan fungsi hati akibat paparan pestisida. Selain itu, Samosir et al (2017) menyatakan adanya gangguan keseimbangan terhadap tubuh petani akibat pajanan pestisida. Dampak penggunaan pestisida terhadap lingkungan di antaranya mencemari tanah, air, dan dapat membunuh organisme yang bukan sasaran (Aktar et al 2009).…”
unclassified